Comprehensive Analysis of lncRNA Expression Pattern and lncRNA–miRNA–mRNA Network in a Rat Model with Cavernous Nerve Injury Erectile Dysfunction. Issue 9 (13th July 2020) - Cong, Rong; Wang, Yi; Wang, Yamin; Zhang, Qijie; Zhou, Xiang; Ji, Chengjian; Yao, Liangyu; Song, Ninghong; Meng, Xianghu
Abstract: Background: Long noncoding RNAs (lncRNAs) are differentially expressed in erectile dysfunction (ED) associated with aging and diabetes mellitus; however, the lncRNA expression profile in cavernous nerve (CN) injury–related ED (CNI-ED) is unknown. Aim: To investigate the dysregulated lncRNAs, microRNAs (miRNAs), and mRNA expression in CNI-ED and construct a potential lncRNA–miRNA–mRNA network. Methods: 22 male Sprague–Dawley (SD) rats were divided into bilateral CN crush (BCNC) and Sham groups. Using second-generation high-throughput sequencing technology, we analyzed the expression profiles of lncRNA, miRNA, and mRNA of the 2 groups. 17 differentially expressed lncRNAs were selected and further validated by quantitative real-time polymerase chain reaction (RT-qPCR). The lncRNA–miRNA–mRNA network, Gene Ontology (GO) term enrichment, and Kyoto Encyclopedia of Genes and Genomes (KEGG) pathway analyses were performed using Cytoscape. Outcomes: Intra-cavernosal pressure, mean arterial pressure, smooth muscle content, and the expression of miRNA, mRNA, and lncRNA were measured. Results: The BCNC group showed decreased intra-cavernosal/mean arterial pressure as well as decreased smooth muscle/collagen ratios compared with the Sham group. The RNA sequencing results revealed dysregulated expressions of 65 lncRNA, 14 miRNA, and 750 mRNA in the BCNC group based on the following criteria: fold change >2 and P < .05. Among the 17 lncRNAs further selected based on mean count number >4 in both groups, 3 lncRNAs (TCONS_00028173, TCONS_00049985, and TCONS_00058429) were further validated for differential expression by RT-qPCR. GO analysis suggests that these 3 lncRNAs could regulate various processes such as myotube differentiation and muscle cell differentiation. Furthermore, the KEGG pathway analysis showed that the mRNAs in the competing endogenous RNA (ceRNA) network are involved in pathways, including axon guidance and vascular endothelial growth factor signaling pathway. Clinical Translation: Our findings may provide new information on molecular pathophysiology of CNI-ED and suggest further research to find a more effective therapy for CNI-ED. Strengths & Limitations: This study is the first to identify the lncRNA expression pattern and propose a ceRNA network in a rat model with cavernous nerve injury–related erectile dysfunction. However, analogous studies are needed to confirm these findings in humans. In addition, we constructed the network by only confirming the lncRNA. Conclusion: Our study reveals differential expression profiles of lncRNAs, miRNAs, and mRNAs between the BCNC and Sham groups and suggests that these differentially expressed lncRNAs may play critical roles in CNI-ED by regulating apoptosis and fibrosis in the corpus cavernosum via targeting mRNAs or miRNAs.